Processamento de dados sísmicos reais da região amazônica - GOMES, Anderson Batista (Universidade Federal do Pará, 2019)
The treatment of seismic data is divided basically in three parts: preprocessing and processing an imaging. In the present thesis we discuss the stages of preprocessing and two important methods of processing directed to the simulation of zero offset (ZO) sections from multiple coverage data. Conventional (NMO/DMO) processing, and the Common Reflection Surface (CRS) processing have been applied to seismic data from some seismic lines of group 204 of the data set of the Tacutu Graben (Brazil). We used the CWP/SU System to carried out the stages of preprocessing and the stage of conventional (NMO/DMO) processing. The CRS processing was carried out with WIT/CRS System. The stages of preprocessing consisted basically of three parts: organization of the geometry; zeroing and muting of noisy traces; and filtering in the temporal frequency (f filter) and velocity filter (f-k filter). Deconvolution was carried out, however due to results that did not bring any information; the results were not of further use. Besides, the elevation static correction was not applied because the topography is very smooth (elevation variation less than 20 m) in Tacutu plateau. The quality of the results of NMO/DMO processing was strongly biased due to the dependence of the method on a velocity model, that in this case it was accurate enough. We also found difficulties with the velocity analysis (VA) due to great amount of noise present in the data. As a consequence, the normal moveout correction (NMO) and migration did not generate better results. Based on the estimated attributes of the CRS stack method, a smooth macrovelocity model was obtained using reflection tomographic inversion. Using this macro-model, pre- and post- stack depth migration were carried out. Also, the CRS attributes are used in the method residual static correction, and the results demonstrate a better resolution of the stacked section. The sections resulting from stack and migration have been interpreted aiming at the delineation of structures. From the visual details of the panels, we have interpreted thinning, a main faulted anticline and discontinuity, and plays of horsts and grabens, and rollovers were traced. On the other hand, the basement could not easily be traced.